Green extraction, chemical profile and biological activity of waste products from the olive oil industry: From waste to wealth - Miryam Perrucci; Marco Dezio; Hammad Saleem; Fabrizio Ruggieri; Marcello Locatelli (Journal of Chromatography Open, 2024)
Olive oil is the most used vegetable oil for human consumption and its production represents an important economic sector, especially in Mediterranean countries. Olive trees are grown in more than 40 countries around the world on over 10 million hectares. The milling industry generates large quantities of liquid and solid residues, the disposal of which requires sophisticated and rather expensive procedures, given the polluting characteristics of the processing products. Since a considerable measure of olive-derived biomass is generated each year, it could be used as a potential source of bioactive compounds. This work evaluates the possibility of recovering natural antioxidants from by-products of the olive oil mill, through the optimization of extraction processes with green approaches. In the present work, through HPLC-PDA analysis with a validated method, it was possible to characterize a chemical profile of the extracts obtained through an optimized (DoE) and green approach. The waste products of the olive oil companies represent the samples considered in this work, and are derived from the pomace and the washing water of 2-phases, 2.5-phases, and 3-phase extra virgin olive oil (EVO) production plants. The optimized extraction methodology, starting from the 2.5-phase olive pomace, proved to be satisfactory in terms of efficiency by evaluating the effect of parameters such as extraction time and process temperature. The application of this methodology to other types of pomace and agro-industrial by-products has highlighted excellent results in terms of extraction yield, demonstrating the validity of this procedure as also suitable for other solid residues coming from the olive oil mill. Regarding the treatment in vegetation water, the developed protocol allowed the chromatographic profile of the analytes extracted from this matrix to be evaluated, leading to satisfactory results in terms of quantitative yields. Samples of these extracts are also subjected to biological tests in order to evaluate their antioxidant and enzyme inhibition activities.